Dynamic Echocardiographic Imaging of a Valve-in-Valve Mitral Prosthesis. (16th February 2022) - Wassef, Bishoy; Masry, Mina; Ghali, Mounir; Makaryus, John N.; Makaryus, Amgad N.
Abstract : Dynamic imaging of heart valves and specifically prosthetic valves is a central benefit of echocardiography. Most bioprosthetic heart valves degenerate over a given time and hence require repeat valve replacement which carries a significant risk of morbidity and mortality. Reoperation is the standard of care and may still be required after the first successful surgery due to complications disrupting either mechanical or bioprosthetic valves. Such complications can be delayed or even prevented if optimal prosthesis selection is individualized according to patients' medical and postimplantation follow-up. We present the case of an 84-year-old woman where an open-heart valve-in-valve approach, implanting a mechanical valve in a failed bioprosthetic valve, produced a unique image on transthoracic echocardiography which needs to be recognized by imagers for appropriate patient diagnosis and management.